(untitled) (Studia Prawnicze / The Legal Studies, 2011)
Do problemów o szczególnym znaczeniu dla prawidłowego funkcjonowania prasy należy kwestia rzetelności wypowiedzi w kontekście odpowiedzialności prasy za naruszenie dóbr osobistych spowodowanych opublikowaniem materiału prasowego. Dla kwestii odpowiedzialności dziennikarza zasadnicze znaczenie ma art.12 prawa prasowego formułujący obowiązek szczególnej staranności. Miara ponadprzeciętnej staranności nasuwa pytanie o wzorzec przeciętnie przezornego dziennikarza. W doktrynie wyłoniło się pytanie, czy niezachowanie należytej staranności stanowi o bezprawności działania lub zaniechania sprawcy szkody, czy też o jego winie. Wcześniejsze zapatrywania doktryny stały na stanowisku, że “miarę dbałego i ostrożnego zachowania” z bezprawnością nie wolno utożsamiać. Jednakże można w tej kwestii wyrazić zapatrywanie odmienne. Despite a difference in opinions held by the jurisdiction and the doctrine, the criterion of special care and reliability should be recognized as one of the circumstances resulting in finding a journalist’s activity lawful or unlawful. We could support the opinion according to which failure to maintain special care belongs to the sphere of unlawfulness (not guilt) since a valid legal system obliges a journalist to act with particularly special care. It is ofmost importance to create some rules of conduct, objective criteria, and more or less precise model of a journalist’s profession. By far a point of reference is necessary which would serve as a comparative scale for those accused of violation so that they could be formally charged. An action will be found blameworthy if a required level of care has not beenmaintained. If a journalist observed the rules of special care while collecting, verifying and publishing information, even though their conduct violated personal interests of a person described in the publication, such conduct will not be considered unlawful. A model of careful and diligent action is formulated by legal provisions, decorum or deontological principles. Journalists are required to be better prepared for their duties, which include not only proving subjective circumstances but also showing objective elements according to which someone’s behavior was consistent with the state of special knowledge and life experience. Such a person is obliged to constantly broaden their knowledge and professional skills. Journalists are obliged to perform all possible actions requiring specialist professional qualifications connected with seeking the truth reliably and conscientiously, with due criticism and care of details. Journalists may not disseminate false, unreliable or unverified information; otherwise their actions will be consider edunlawful. A duty of reliability means the obligation to seek for the truth and rational argumentation while making a negative evaluation. The above actions generally refer to the factual and legal state as well as the form of working. Remissness of due care and professional reliability may constitute the grounds for professional or civil liability (including criminal liability). The introduction of this requirement, which results from a journalist duty to seek for the truth, is justified by the protection of the object of special importance, which personal interests undeniably are. The obligation to maintain special care generally takes effect in truthfulness of presented facts. If the news appeared to be false, there is a possibility of applying a circumstance excluding liability if a journalist proved that in that case he had verified the authenticity of the news which was published. Thus liability is avoided and the proof of the news’ authenticity is replaced by the duty of its thorough verification, i.e. maintenance of the rule of special care. The resolution of the Supreme Court of 18th February 2005, which was criticized by the doctrine, abandoned a theory according to which an “objectively untrue” statement is unlawful. Nevertheless, this attitude is in line with the European Court of Human Rights’ way of thinking. Maintenance of special care and reliability while collecting and using press materials by journalists (Art. 12 par. 1 of the media law) excludes the feature of unlawfulness of a journalist action. Moreover, it should be noticed that proving that charges are right is not always a necessary and independent prerequisite to exclude liability of a person violating personal interests (e.g. in the sphere of privacy).